LIQUID CHROMATOGRAPHY DEPENDENT STABILITY INDICATING METHODOLOGY: DEVELOPMENT AND AUTHENTICATION FOR FORMULATIONS OF CAPSULE TYPE CONTAINING TEGAFUR, GIMERACIL, AND OTERACIL - HARITHA KUMARI, MAILAMURI; KHANDAPU, BALA MURALI KRISHNA; RAJU, RUDRARAJU RAMESH (International Journal of Applied Pharmaceutics, 2023)
Objective: This investigation entitles the development and authentication of a rapid, selective and explicit RP-HPLC technique to assay tegafur (TGR), gimeracil (GMR), and oteracil (OTR) simultaneously in bulk and formulations of capsule type. Methods: The separation, detection and assessment of TGR, GMR and OTR were achieved using a C18 Agilent Zorbax (25 cm; 4.6 mm; 5 µm particle dimension) reverse phase column. The acetonitrile (40% by volume) and 0.1% triethylamine in distilled water (pH 2.5, 60% by volume) was utilized as mobile phase. The validation of the method and degradation study was performed as per the strategy given by ICH. Results: The retention periods in Agilent Zorbax column for OTR, TGR, and GMR were 2.458 min, 7.236 min and 8.629 min, respectively. Linearity was seen in the concentration series of 5.0-30.0 µg/ml (TGR), 1.45-8.70 µg/ml (GMR), and 3.95-23.70 µg/ml (OTR). The regression coefficient was greater than 0.999. The LOQ values were 0.606 µg/ml (TGR), 0.175 µg/ml (GMR), and 0.478 µg/ml (OTR). The percent comparative standard deviation (exactness) values were bestowed to be 0.243%-0.676%, 0.293%-1.894% and 0.269%-0.615% for TGR, GMR and OTR, respectively. The percent recoveries (accuracy) were in the range of 100.044%-100.493 for TGR, 99.730%-100.335% for GMR and 100.064%-100.543% for OTR. Conclusion: The research results of the degradation investigation proved the technique's specificity as well as stability indicating feature. The process could be used for routine evaluation of OTR, TGR, and GMR in formulations of capsule type.